Sosialisasi dan Pelatihan Akuntansi untuk Penyusutan Aset Tetap pada BUMDes Amanah Desa Bukit Gajah Kecamatan Ukui Kabupaten Palalawan Riau - Sanda Patrisia Komalasari; Fitriyeni Oktavia; Berri Brilliant Albar; Ares Albirru Amsal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
This activity aims to provide socialization and training regarding the depreciation of fixed assets to village-owned enterprises called BUMDes Amanah Bukit Gajah, Palalawan Regency, Riau. It was due to that BUMDes have never depreciated their fixed assets at all. Depreciating fixed assets owned by BUMDes will improve the current quality of financial reporting. This activity began with understanding the business of BUMDes. Then it continues with the provision of training and pilots following existing cases in BUMDes, including compiling tables and making sheets of Microsoft Excel-based depreciation calculators needed by BUMDes. This activity was attended by 5 BUMDes employees responsible for financial reporting. The depreciation method and useful life of fixed assets will be adjusted to tax regulations. The result of this activity was in the form of the socialization of fixed assets and their depreciation.